Integrating Family-Based Science Education to Support Patient Resilience: A Study on Hemodialysis Patients in Pidie Regency - Kartika Kartika; Idawati Idawati; Yuliana Yuliana; Ismuntania Ismuntania; Fakhryan Rakhman (Jurnal Penelitian Pendidikan IPA, 2025)
Chronic kidney disease is one of the health problems that has been widespread and reaches 5-10% of the human population. According to data from the Basic Health Research (Riskesdas) in 2018, the prevalence of chronic kidney disease in Indonesia is around 0.2%, with the highest prevalence in Central Sulawesi at around 0.5%. The treatment procedure for kidney failure is a kidney transplant or hemodialysis therapy. However, due to the difficulty of finding a kidney donor, hemodialysis therapy is an option. This therapy is a dialysis therapy that is done twice a week. This makes patients have psychological disorders such as stress, depression, anxiety disorders, and even suicidal thoughts. This disorder will certainly affect the patient's level of resilience, so it is necessary to have science education provided by the families in the form of health literacy, treatment knowledge, and emotional support to increase the patient's self-resilience. The research method used is a quantitative method by using cross sectional, namely data observation is carried out at one time. The research data were obtained through a questionnaire consisting of a family science education questionnaire and patient resilience. The results showed that the existence of science education provided by families in the form of health literacy, treatment knowledge, and emotional support plays a critical role in enhancing patients’ resilience during hemodialysis. A good level of resilience in patients can improve the quality of life and physical activity of patients